EP-116 Family and Next of Kin (NOK) Communication - Time for a new NELA standard?. (9th August 2022) - Ahmed, Salma; Hassan, Karim; Abubaker, Malaz; Wilson, Jeremy; Magee, Conor
Abstract: Introduction: The Covid-19 pandemic highlighted the importance of communication between patients, families, and the surgical team. Covid left many patients bereft of personal contact with loved ones and NOK were often left without information due to overwhelming, challenging situations for surgical teams. These challenges may not be unique to Covid- e.g team shift-working, late-night operating are ongoing barriers to NOK communication following emergency laparotomy (EmLap). Methods: Twenty random EmLap patients during the pandemic were identified. Qualitative data on NOK discussion were obtained including telephone follow-up to confirm whether discussions took place. Results: Only 50% of patients had documented NOK discussion- of these seven were held prior to surgery, 4 post-operatively and 5 during admission. Communication with families was mainly carried out by nurses while consultant/registrar discussions were documented on 7 occasions only. Conclusion: Communication with the NOK of patients undergoing emergency laparotomy needs improving. Patient-centred care must involve the NOK. We would suggest that NOK should be informed of surgical outcomes and prognosis by a senior surgical team member. Notwithstanding the usual caveats of confidentiality and patient wishes- the importance of this facet of surgical care to many patients and their relatives cannot be understated and could be considered as a potential NELA standard of care.